Characterization of gas-liquid flows in annuli. - Eyo, Edem Nsefik (Cranfield University, 2019)
Gas–liquid two–phase flow in annulus is encountered during certain operations in the nuclear, chemical and petroleum industries. In the Oil and Gas industry, the knowledge of gas liquid two-phase flow in annuli is important during underbalanced drilling of wells and hole clean operations. This technique offers several advantages over the conventional drilling method including reducing formation damage, preventing fluid losses and enhancing the safety and efficiency of operation. Proper design of underbalanced drilling operations hinges on the accurate prediction and monitoring of gas-liquid two-phase flow parameters such as flow regimes, liquid holdup and pressure drop; however the complexities associated with two-phase flows coupled with complex geometry makes this difficult. Limited studies exist in literature for gas-liquid flow hydraulics in horizontal annuli and no studies have been undertaken on the effects of annulus eccentricity on two-phase flow parameters including flow regimes, liquid holdup and pressure drop. In order to provide an improved fundamental understanding of gas-liquid two-phase flow in horizontal annulus and give insight necessary for accurate model development, detailed systematic experimental studies are conducted at atmospheric conditions in horizontal concentric and fully eccentric annulus formed using a 3 inch outer and 2 inch inner pipes. Flow parameters including flow regimes, liquid holdup and pressure drop are investigated using high speed camera, conductance probes and pressure transducers, with air and water as testing fluids. Results show that annulus eccentricity affects the flow regimes, liquid holdup and pressure drop. Predictive models are compared with experimental data and new models are proposed for flow regime identification and liquid holdup prediction, while a new real-time objective flow regime identification tool is developed using Support Vector Machine (SVM). The data generated from this study can be used for developing models which would be incorporated into commercial software for study of flow through annulus.
Keywords: Concentric; eccentricity; flow regimes; liquid holdup; pressure drop; drilling